2014
DOI: 10.1007/s11606-014-2801-5
|View full text |Cite
|
Sign up to set email alerts
|

Entrustment and Mapping of Observable Practice Activities for Resident Assessment

Abstract: Entrustable Professional Activities (EPAs) and the Next Accreditation System reporting milestones reduce general competencies into smaller evaluable parts. However, some EPAs and reporting milestones may be too broad to use as direct assessment tools. We describe our internal medicine residency curriculum and assessment system, which uses entrustment and mapping of observable practice activities (OPAs) for resident assessment. We created discrete OPAs for each resident rotation and learning experience. In comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 14 publications
1
101
0
Order By: Relevance
“…22 Another approach is to define smaller units of activities that nest together within larger EPAs, as has been proposed with Observable Professional Activities. 23 Our approach to EPA development and mapping to milestones has limitations. This work occurred at a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another approach is to define smaller units of activities that nest together within larger EPAs, as has been proposed with Observable Professional Activities. 23 Our approach to EPA development and mapping to milestones has limitations. This work occurred at a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] Compared to our review of the 2013 literature relevant to general medicine educators, 26 we found more multi-institutional studies of high quality. Similar to last year, resident continuity clinic and handoffs were areas of focus.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,19,25 We also found descriptive studies on use of the milestone-based learner assessments. 18 Our selection process prioritized those most relevant, important, and generalizable, and with greatest methodological quality, for our audience of general internist educators.…”
Section: Discussionmentioning
confidence: 99%
“…OPAs differ from EPAs in that they are more context or content specific than EPAs, but are used in a similar manner to EPAs for learner assessment. 10 Observable practice activities were originally described as a way to assess learners' observed performance, which in turn serves to inform entrustment within EPAs. 10 However, EPAs expand beyond OPAs, by addressing activities that society trusts all physicians to do, 5 and by allowing assessment of these activities over the course of a resident's training.…”
Section: Introductionmentioning
confidence: 99%